Interview with Mark Dutcher, artist, Los Angeles, 5 April 2013 - Messham-Muir, Kit (StudioCrasher, 2015)
Mark Dutcher is a Los Angeles-based artist. He works primarily in painting and in this interview we discuss the influence of music on his work, the role of abstraction in contemporary art, and Mark talks about specific works in his studio.